Analisis Implementasi Kebijakan Pengawasan Wajib Pajak Pasca Periode Pengampunan Pajak Dalam Rangka Kepatuhan Wajib Pajak Di KPP Jakarta Duren Sawit - Ratu, Ariesta Fransisco; Ramdan, Alief (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Tax amnesty is a government policy to provide a free-pass for taxpayers to disclose incomplete or unreported income in their previous tax periods without having to face prosecution by the tax court or pay any penalty. The level of compliance of taxpayers at KPP Jakarta Duren Sawit from 2015 - 2019 was still below 80%, therefore the Directorate General of Taxes (DGT) emphasized the supervision and monitoring mechanism for the supervision of taxpayer compliance after the tax amnesty period. The target of supervision remained to be all taxpayers, both those who participated in the tax amnesty program and those who did not. This study aims to analyze the implementation of taxpayer supervision policies after the tax amnesty period in order to improve taxpayer compliance at KPP Jakarta Duren Sawit. The analytical method used was descriptive qualitative. The results show that the taxpayer supervision policies after the tax amnesty period in order to improve taxpayer compliance at KPP Jakarta Duren Sawit has been implemented well. Communication is integrated through the e-performance application so that all supervisory activities can be carried out immediately, resources have been prepared long before the tax amnesty, the disposition of the implementer has followed the applicable code of conduct, and the standard operating procedures are in accordance with policies and are not too complicated.